A petrogenetic model for the comagmatic origin of chassignites and nakhlites: Inferences from chlorine‐rich minerals, petrology, and geochemistry. (1st April 2013) - McCubbin, Francis M.; Elardo, Stephen M.; Shearer, Charles K.; Smirnov, Alexander; Hauri, Erik H.; Draper, David S.
Abstract Twelve samples belonging to the chassignite and nakhlite subgroups of Martian meteorites were investigated using a variety of micro‐beam analytical techniques to gain insight into the petrogenesis of these two meteorite classes. There are a striking number of geochemical similarities between the chassignites and nakhlites, including mineralogy and petrology, crystallization age, cosmic‐ray exposure age, and radiogenic isotopic compositions. However, there are also geochemical differences, namely in trace element systematics of pyroxenes, that have led some authors to conclude that the nakhlites are comagmatic with each other, but not comagmatic with the chassignites. On the basis of data presented here, we propose a model in which these differences can be reconciled by the addition of an exogenous Cl‐rich fluid to the chassignite‐nakhlite magma body shortly after the formation of the cumulate horizon that was sampled by the Chassigny meteorite. This model is supported by the textural and chemical associations of the volatile‐bearing minerals apatite, amphibole, and biotite, which record a history starting with the addition of a Cl‐ and LREE‐enriched fluid to the magma body. As the magma continued to crystallize, it eventually reached chloride saturation and degassed a Cl‐rich fluid phase. Depending on the provenance of the Cl‐rich fluid, this model could explain how the chassignites and nakhlites originated from an LREE‐depleted source, yet all exhibit LREE‐enriched bulk‐rock patterns. Additionally, the model explains the range in oxygen fugacity that is recorded by the chassignites and nakhlites because eventual exsolution and loss of Cl‐rich fluid phases near the end of crystallization of the nakhlite sequence leads to auto‐oxidation of the magma body due to the preferential partitioning of Fe2+ into the fluid phase.